Pengaturan Hukum Tentang Tindak Pidana Cyberstalking Terhadap Pejabat Penting Negara di Sulawesi Selatan - Martono; Andi Bau Ria Anugrah; Ismail Ali; Andi Nail Ijlal Zaki (Legal Journal of Law, 2026)
This study aims to determine the form of regulation regarding the criminal act of spreading cyberstalking based on the provisions of the articles in the ITE Law and the Criminal Code, and to determine the factors that hinder law enforcement against this crime. The research method used is a normative-empirical legal approach by combining analysis of laws and regulations and field data. Primary data was obtained through interviews with investigators at the South Sulawesi Regional Police, while secondary data was obtained from legal literature, scientific journals, and relevant laws and regulations. Data analysis techniques were carried out qualitatively by examining the conformity between legal norms and law enforcement practices in the field. The results of the study indicate that normatively the spread of cyberstalking links can be ensnared through several provisions in the ITE Law and the Criminal Code, including Law Number 1 of 2008 and Law Number 1 of 2023 relating to the dissemination of misleading information, illegal access to electronic systems, and stalking. However, various obstacles remain in law enforcement practice, such as difficulties in obtaining digital evidence, the use of anonymous perpetrator identities, limited digital forensic technology, the absence of victims willing to report, and low public awareness of safeguarding electronic evidence. These findings indicate a gap between applicable legal norms and their implementation in law enforcement practice. Although a legal framework for prosecuting cyberstalkers is available in the ITE Law and the Criminal Code, its effective implementation still requires strengthening through capacity building of law enforcement officers, provision of digital investigative technology, and increased public digital literacy.